Bird migration in space and time: chain migration by Eurasian curlew Numenius arquata arquata along the East Atlantic Flyway - Pederson, Rebecca Mallory; Bocher, Pierrick; Garthe, Stefan; Fort, Jérôme; Mercker, Moritz; Auernhammer, Verena; Boschert, Martin; Delaporte, Philippe; Elts, Jaanus; Fiedler, Wolfgang; Korniluk, Michał; Krupiński, Dominik; et al. (Journal of Avian Biology, 2022)
Migration patterns in birds vary in space and time. Spatial patterns include chain, leapfrog and telescopic migration. Temporal patterns such as migration duration, number, and duration of stopovers may vary according to breeding latitude, sex, and season. This study aimed to verify these patterns in a long-distance migrant, the Eurasian curlew Numenius arquata arquata, and to provide a synopsis of spatio-temporal migration patterns in this species of concern throughout the East Atlantic Flyway. We tagged 85 adults with GPS-data loggers in Germany, Poland, France and Estonia between 2013 and 2019. We computed the distance flown, linear loxodromic distance, duration, stopover number, total stopover duration, mean stopover duration, departure time and arrival time for 177 out of 187 tracks. On average (± standard deviation), spring migration occurred from 4 to 14 April (10.2 ± 8.4 days), curlews flew 3.623 ± 1.366 km, and had 5.8 ± 3.6 stopovers, with a duration of 29.4 ± 38.2 h per stopover, while autumn migration occurred from 18 to 29 June (10.9 ± 9.9 days), curlews flew 3.362 ± 1.351 km, and had 5.4 ± 4.0 stopovers, with 31.8 ± 32.3 h per stopover. Curlews displayed chain migration because wintering curlews maintained the latitudinal sequence to their breeding sites. Southern curlews had a longer nesting period due to their earlier arrivals. While spring arrival at breeding sites did not differ between the sexes, in autumn females departed earlier than males. Migration duration and distance, as well as stopover number and duration, showed a significant increase with breeding site latitude but did not differ between the sexes or between spring and autumn migrations, suggesting that curlews took a comparable amount of time migrating during both seasons. The high site faithfulness in curlews suggests that rapid autumn migration allows them to return to defend their winter foraging areas.